Konkurenceschopnost podniku na prahu nového tisíciletí - Kožená, Marcela (Univerzita Pardubice, 2004)
The competition ability of the enterprise is most discussed theme nowadays. The world-widetrend is nowadays globalisation process, which generates continually more complicated the competitive environment for enterprises. The aim of this article is the definition of the conception "the competitive ability of enterprise", which comes out of many Czech and foreign authors.
Keywords: Konkurenceschopnost; podniky; konkurenční strategie